He was some kind of a man : masculinities in the B western - McGillis, Roderick (Film + media studies., 2009)
He Was Some Kind of a Man: Masculinities in the B Western explores the construction and representation of masculinity in low-budget western movies made from the 1930s to the early 1950s. These films contained some of the mid-twentieth-century's most familiar names, especially for youngsters: cowboys such as Roy Rogers, Hopalong Cassidy, and Red Ryder. The first serious study of a body of films that was central to the youth of two generations, He Was Some Kind of a Man combines the author's childhood fascination with this genre with an interdisciplinary scholarly exploration of the films influ.